Lipid profile and associated factors in schoolchildren - De Oliveira Azambuja, Ana Paula [UNESP] (My University, 2017)
The relationship between anthropometric measurements and lifestyle habits of schoolchildren with lipid profile is assessed by a descriptive, cross-sectional study on a sample of 135 school children aged between 6 and 10 years. Variables comprised body mass index, waist circumference, blood pressure, questionnaires on physical activity, dietary habits and metabolic changes. Analysis compares rates by Mann-Whitney test and associations by chi-square test, while effects were measured by odds ratio at 5% significance (p <0.05). There was no significant association between nutritional status and lipid profile. Lipid changes occurred inclusively in children with normal weight. Physical activity was inversely associated with dyslipidemia and suggests that physical activities associated with eating habits may be a preventive mechanism on cardiovascular disease risk factors.
Keywords: Children; Dyslipidemia; Food habits; Obesity